Aging does not impact drug--drug interaction magnitudes with antiretrovirals. (1st May 2020) - Stader, Felix; Decosterd, Laurent; Stoeckle, Marcel; Cavassini, Matthias; Battegay, Manuel; Saldanha, Susana Alves; Marzolini, Catia; Courlet, Perrine
Abstract : N/A: The risk of drug–drug interactions (DDIs) is elevated in aging people living with HIV (PLWH) because of highly prevalent age-related comorbidities leading to more comedications. To investigate the impact of aging on DDI magnitudes between comedications (amlodipine, atorvastatin, rosuvastatin) and boosted darunavir, we conducted a clinical trial in aging PLWH aged at least 55 years. DDI magnitudes were comparable with those reported in young individuals supporting that the clinical management of DDIs in aging PLWH can be similar.